CHEMICAL CHARACTERISTICS AND GELLING PROPERTIES OF AGAR EXTRACTED FROM RED ALGAE GROWING AT VIETNAM COAST - Van, Tran Thi Thanh; Hau, Le Nhu; Hieu, Vo Mai Nhu; An, Luu Phuoc; Ly, Bui Minh (Vietnam Journal of Marine Science and Technology, 2006)
CHEMICAL CHARACTERISTICS AND GELLING PROPERTIES OF AGAR EXTRACTED FROM RED ALGAE GROWING AT VIETNAM COAST